1991
DOI: 10.1007/bf02457635
|View full text |Cite
|
Sign up to set email alerts
|

Follistatin inhibits the mesoderm-inducing activity of activin A and the vegetalizing factor from chicken embryo

Abstract: The induction of mesoderm is an important process in early amphibian development. In recent studies, activin has become an effective candidate for a natural mesoderm-inducing factor. In the present study, we show that follistatin, an activin-binding protein purified from porcine ovary, inhibits the mesoderm-inducing activity of recombinant human activin A (rh activin A), which is identical to the erythroid differentiation factor (EDF). The quantity of follistatin required for effective suppression of activin w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

1991
1991
1999
1999

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 60 publications
(17 citation statements)
references
References 35 publications
0
17
0
Order By: Relevance
“…The cDNA sequence of each subunit and follistatin was identical to the corresponding region of rat mhibm. actlvin [2] and folhstatin [14]. respectively.…”
Section: Rt-pcr and Sequencrngmentioning
confidence: 99%
“…The cDNA sequence of each subunit and follistatin was identical to the corresponding region of rat mhibm. actlvin [2] and folhstatin [14]. respectively.…”
Section: Rt-pcr and Sequencrngmentioning
confidence: 99%
“…Follistatin binds to both inhibin and activin through the common b subunit (18). Neutralization of activin's activity by follistatin is proven in various systems, such as the stimulation of FSH secretion in cultured pituitary cells (8), induction of mesoderm tissue formation in Xenopus oocytes (19), and differentiation of rat granulosa cells (20). These results indicated that follistatin is a functional regulator of activin's activity.…”
Section: Introductionmentioning
confidence: 99%
“…The injected cells express chordin mRNA (Rebbert & David 1997). Zygotic transcripts of cerberus accumulate in the Xenopus embryo 1 h later than those of chordin (Bouwmeester et al 1996) (Glinka et al 1998 (Asashima et al 1991;Grunz 1996).…”
Section: Partial Purification Of a Neuralizing Factor From The Cytosolmentioning
confidence: 99%